Improving Mathematical Reasoning Ability by Developing Mathematical Learning Tools Based on Guided Discovery Models - Randika Irwa Risky; Hendra Syarifuddin; I Made Arnawa; Suherman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Junior high school students low mathematical reasoning ability is one reason for carrying out this research. This study aims to produce a valid, practical, and effective Guided Discovery-based Mathematics Learning Tool to facilitate students' mathematical reasoning abilities. This study is development research carried out with the Plomp development model. This model has three stages: preliminary investigation, prototyping stage, and assessment phase. This research was conducted at SMP Negeri 4 Padang. The instruments used to collect data are questionnaires, documentation, test questions, and interviews—data analysis using quantitative and qualitative data analysis techniques. The results showed that the Guided Discovery-based Mathematics Learning Toolkit developed was categorized as valid (3.30 for RPP and 3.35 for LKPD) and very practical, respectively, 82.6% and 85% (for RPP and LKPD). Meanwhile, based on the results of the test results of the mathematical reasoning ability test, it was found that 86.3% of students met the criteria for the success of the mathematical reasoning ability test > 80%, meaning that the guided discovery model-based learning device was very influential on mathematical reasoning abilities.